Television Viewing in Low-Income Latino Children: Variation by Ethnic Subgroup and English Proficiency - Thompson, Darcy A. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Television viewing is associated with an increased risk for obesity in children. Latino children are at high risk for obesity and yet little is known about differences in television viewing habits within this population. The purpose of this study is to determine if hours of television viewed by young children with low-income Latina mothers differs by maternal ethnic subgroup and English language proficiency. METHODS: This was a cross-sectional analysis of data from the Welfare, Children, & Families: A Three City Study. Participants were 422 low-income Latina mothers of Mexican and Puerto Rican descent with children ages 0–4 years old. The dependent variable was hours of daily television viewed by the child. The independent variable was maternal ethnic subgroup and English language proficiency. Analyses involved the use of multiple negative binomial regression models, which were adjusted for demographic variables. RESULTS: Multivariable regression analyses showed that compared to children with mothers of Mexican descent, children of mothers of Puerto Rican descent watch more daily television (<2 years old, incidence rate ratio (IRR)=4.18, 95% confidence interval (CI) 1.68, 10.42; 2–4 years, IRR=1.54, 95% CI 1.06, 2.26). For children with mothers of Mexican descent, higher maternal English language proficiency was associated with higher amounts of child television viewing (IRR=1.29, 95% CI 1.04, 1.61). No relationship was found for children of Puerto Rican descent. CONCLUSIONS: Child television viewing varies in low-income Latino children by maternal ethnic subgroup and English language proficiency. Interventionists must consider the varying sociocultural contexts of Latino children and their influence on television viewing.